The Effect of Using the Duolingo Application on English Learning Outcomes of Third-Grade Students at SD Negeri 10 Sitiung - Zumrotun Lutfiah; Riyadi Saputra; Riandini Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The limitation of English learning outcomes for third-grade students at SD Negeri 10 Sitiung serves as the basis for this study. The aim of this research is to examine the impact of using the Duolingo application on student achievement in this subject during the 2024/2025 academic year. The use of interactive and engaging learning media such as Duolingo is considered to have the potential to improve students' performance. This study adopts a quantitative approach with a one-group pretest-posttest design, involving 16 third-grade students from SD Negeri 10 Sitiung as the sample. Data were collected using a multiple-choice test instrument administered before and after the intervention. Data analysis was conducted through normality tests and hypothesis testing. Based on the results of the normality test, the significance value of the pretest data was 0.179 (>0.05) and the posttest data was 0.164 (>0.05). Meanwhile, the hypothesis test results using the paired samples test showed a significance value of 0.000, which is less than 0.05. These findings indicate that the null hypothesis (H0), which states there is no effect, is rejected, and the alternative hypothesis (Ha), which states that there is a significant effect of using the Duolingo application, is accepted. Therefore, it can be concluded that the use of the Duolingo application has a significant effect on improving the English learning outcomes of third-grade students at SD Negeri 10 Sitiung.